Principles of Facial Hygiene: Strategies for Preserving Dermatological Health (CIPEEX, 2025)
INTRODUCTION: Skin care goes far beyond aesthetics: it is also about preserving your skin's health, well-being, and natural functionality. Daily facial cleansing, when done correctly and with the right products, is one of the most important steps in this process. On a daily basis, the skin on your face is constantly exposed to pollutants, makeup, oiliness, and solar radiation—elements that, when accumulated, can trigger various dermatological problems. Removing these impurities not only prevents conditions such as acne and irritation, but also contributes to a more uniform and vibrant appearance of the skin.OBJECTIVE: The objective of this study is to investigate how facial cleansing, when integrated into a well-structured and a personalized routine, positively influences the maintenance of skin health, vitality, physiological balance, and resistance to external environmental aggressions.METHOD: A literature review was conducted based on recent scientific studies, focusing on articles in the fields of dermatology and aesthetics. The analysis criteria included the correct choice of cleansing products, the ideal frequency of use, the method of application, and the importance of photoprotection after daily facial cleansing.RESULTS: The literature reviewed reinforces that a routine that includes cleansing, moisturizing, and daily sun protection makes a difference not only in skin health but also in its resistance to external factors. Products tailored to each skin type tend to produce better results, especially when combined with continuous use of sunscreen and maintenance of skin pH. These measures, taken together, promote skin balance and integrity.
Keywords: Higienização; Pele; Cuidado; Dermatológico